2020
DOI: 10.3390/coatings10030275
|View full text |Cite
|
Sign up to set email alerts
|

WC-Co and WC-Co-Cr Coatings for the Protection of API Pipeline Steel from Corrosion in 4% NaCl Solution

Abstract: Two inorganic coatings, namely 88%WC-12%Co (PSC1) and 86%WC-10%Co-4%Cr (PSC2), were deposited on the surface of an API-2H pipeline steel using high velocity oxy-fuel deposition. The corrosion of the uncoated and coated API-2H steel after their immersion in a solution of 4.0% NaCl for 1 h, 24 h, and 48 h has been studied. Various electrochemical measurements such cyclic potentiodynamic polarization, electrochemical impedance spectroscopy, and potentiostatic current versus time were employed. The surface morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In the reverse scan curve, all of the coatings showed a negative hysteresis loop at first, followed by positive hysteresis. The areas of the negative hysteresis loops belonging to the E1 and E2 coatings were larger than those of the H1 and H2 coatings, indicating more serious pitting corrosion [25,26]. This is associated with the spherical geometry of WC and corresponds to the coating surface morphology after corrosion, as shown in Figure 10.…”
Section: Potentiodynamic Polarization Testmentioning
confidence: 87%
“…In the reverse scan curve, all of the coatings showed a negative hysteresis loop at first, followed by positive hysteresis. The areas of the negative hysteresis loops belonging to the E1 and E2 coatings were larger than those of the H1 and H2 coatings, indicating more serious pitting corrosion [25,26]. This is associated with the spherical geometry of WC and corresponds to the coating surface morphology after corrosion, as shown in Figure 10.…”
Section: Potentiodynamic Polarization Testmentioning
confidence: 87%
“…One such cermet is WC-10Co-4Cr; this coating was asserted to have better mechanical and corrosion performances than that of other cermet coatings. Sherif et al, used high velocity oxy-fuel (HVOF) coating deposition technique to deposit WC12Co and WC-10Co-4Cr coatings on API-2H pipeline steel, and corrosion tests were conducted on both bare and coated steel substrate by immersing it in 4% NaCl solution for 1, 24, and 48 h [15]. The author concluded that WC-10Co-4Cr cermet coating has provided better corrosion resistance compared to the resistance offered by WC-12Co coating.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, they not only have to transfer huge bit weights and withstand great torsional stress, but they also suffer from erosion, corrosion, and wear during the work process [ 4 , 5 , 6 ]. Drilling fluid could cause the significant erosion and corrosion of a drill pipe, especially saturated saltwater, which is usually applied as drilling fluid in permafrost and salt rock drilling [ 1 , 7 , 8 , 9 , 10 , 11 ]. Moreover, the diameter of the pipe joint is usually larger than that of the drill pipe, resulting in significant wear.…”
Section: Introductionmentioning
confidence: 99%
“…Coating on the surface with excellent wear resistance and good protective effects is considered one of the most effective methods to improve the service performance of components in fields such as agricultural machinery, energy, transportation, chemical industry, and drilling engineering. Hence, a hard coating could be applied to the surface of the drill pipe or joint to improve its anti-corrosion and anti-wear [ 8 , 13 , 14 , 15 , 16 ]. There are several major coating methods to prepare hard coatings, such as high-velocity oxygen–fuel spraying [ 1 , 17 ], cold spraying [ 15 , 18 ], plasma spraying [ 19 ], micro-arc oxidation [ 20 , 21 ], high-speed laser cladding [ 22 ], high-power impulse magnetron sputtering [ 16 ], plasma electrolytic oxidation [ 23 ], and so on [ 13 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation